Effects of COVID-19 on Coffee Market Participation of Smallholder Coffee Producers’ in Godere District, Southwestern Ethiopia - Temesgen Kabeta; Mabiratu Dangia (Advances in Agriculture)
In sub-Saharan countries like Ethiopia, COVID-19 affected not only the health sector, but also the agricultural productivity and marketing, especially affecting coffee producers’ probability of market participation. The study was conducted on the effects of COVID-19 on smallholder coffee producers’ coffee market participation in Godere district, southwestern Ethiopia. This study aimed to identify the effects of COVID-19 on coffee producers, its effect on the decisions of market participation mechanisms, and the prevention mechanisms employed during the pandemic. For this study, qualitative and quantitative data were collected from primary and secondary sources by using a semi-structured interview schedule with well-trained data collectors. The data was analyzed, and a simple random sampling technique was used to select 384 coffee producers at 95% confidence level. The study result shows that the level of coffee producers’ market participation was reduced from 100% to 81.25% because of COVID-19’s effect on smallholder farmers, with 18.75% failing to participate in the coffee market. COVID-19 prevention mechanism provided by the government for social movement was strongly affecting farmer levels of market participation. Most of the coffee producers agreed that COVID-19 affected their probability of coffee market participation because concerned stakeholders in the sector were not well subsidized to recover from the depression. Most of the farmers were not effectively getting financial services from aid organizations and government to mitigate the impact on their livelihood. Generally, COVID-19 strongly affected the levels of coffee producers’ market participation, and it is advisable for concerned bodies to support producers by providing subsidies and creating market linkages.